DEVELOPMENT AND PERFORMANCE EVALUATION OF TUMOR TARGETING POTENTIAL OF FOLATE SPACER FUNCTIONALIZED SOLID LIPID NANOPARTICLES - SINGH, SHIKHA; CHATURVEDI, PRIYANKA; K JAIN, SURENDRA (Asian Journal of Pharmaceutical and Clinical Research, 2021)
Purpose: The objective of the present investigation was to assess the tumor-targeting potential of ligand-spacer engineered solid lipid nanoparticles (SLN) as nanoscale drug delivery units for site-specific delivery of a model anticancer agent, paclitaxel (PTX). SLNs were engineered by direct and indirect conjugation of folic acid (FA) through different types of polyethylene glycols (PEGs) (MW: 1000, 4000) as spacers. Methods: The synthesized nanoconjugates (SLNFA, SLN1FA, and SLN4FA) were characterized by Fourier transform infrared spectroscopy, nuclear magnetic resonance, and transmission electron microscopic studies. Nanoconjugates were evaluated for entrapment, in vitro drug release (under various pH conditions) and hemolytic studies. Cell uptake and cytotoxicity studies were performed on human malignant cell lines (MCF-7) using 3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide assay. Results: This study explored the effect of PEG spacer length on the targeting potential of folate-conjugated SLN. PTX entrapment and in vitro drug release from nanoconjugates augmented, and hemolytic toxicity of nanoconjugates slashed with the molecular weight of PEGs. Further, nanoconjugates with PEG 4000 displayed highest tumor-targeting potential as compared to other spacer conjugated nanoconjugates due to optimized steric hindrance and receptor mediated endocytosis among other PEGs. Conclusion: Engineering of the dendritic surface with targeting ligand such as FA can enhance the site-specific anticancer drug delivery. PEGylation of SLN can improve the circulation time of SLN in the body. This is a debut study reporting FA conjugation to the surface through four PEGs as spacer and optimized the spacer chain length for effective cancer targeting through SLN. This report as a whole is believed to shed new light on the role of spacer chain length in targeting potential of folate-anchored SLN.